History and gender : some explorations - Poonacha, Veena; Shah, Kirit K. (Rawat Publications, 2005)
Gender as genre of history in India is virtually seen to be synonymous with womenâ??s history having originated out of the phenomenon of feminism. Few realize that â??womanâ?? and â??manâ?? both are cultural rather than biological categories, and any history based on this realization would subject to searching enquiry the entire gamut of woman-man relationships in societies across time and space. This all-encompassing nature of the concept underlines its overriding importance among all available models and methods of history. The measure of epistemological crisis it has created might be evident from the fact that the very first paper of present anthology pleads for rejection of the entire corpus of available knowledge having been pervaded, and thus vitiated, by androcentric bias. In view of the pioneering nature of studies and the diverse dimensions of historical reality that they explore, the book will prove to be of fundamental interest to the students and scholars across the entire spectrum of social sciences